A new Brauer-type eigenvalue localization set for tensors. Issue 4 (2nd April 2016) - Li, Chaoqian; Zhou, Jianjun; Li, Yaotang
Abstract : A new Brauer-type eigenvalue localization set for tensors is given. We show that this set is tighter than those provided by Qi (J. Symbolic Comput. 2005 ), Li et al. (Numer. Linear Algebra App. 2014), and Li and Li (Linear and Multilinear Algebra, 2015). Based on this set, we give an upper bound for the spectral radius of nonnegative tensors, and prove that the new bound is sharper than those provided by Yang and Yang (SIAM J. Matrix Anal. App. 2010) and Li et al. (Numer. Linear Algebra App. 2014).